2023
DOI: 10.3389/fimmu.2023.1255478
|View full text |Cite
|
Sign up to set email alerts
|

Niacinamide enhances cathelicidin mediated SARS-CoV-2 membrane disruption

Tanay Bhatt,
Binita Dam,
Sneha Uday Khedkar
et al.

Abstract: The continual emergence of SARS-CoV-2 variants threatens to compromise the effectiveness of worldwide vaccination programs, and highlights the need for complementary strategies for a sustainable containment plan. An effective approach is to mobilize the body’s own antimicrobial peptides (AMPs), to combat SARS-CoV-2 infection and propagation. We have found that human cathelicidin (LL37), an AMP found at epithelial barriers as well as in various bodily fluids, has the capacity to neutralise multiple strains of S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Studies demonstrated that keratinocytes treated with a niacinamide solution were successfully stimulated to synthesize AMPs in vitro, providing protection against skin infection [68]. Furthermore, there is evidence that niacinamide can potentiate the activity of cathelidicin LL-37 [77,79]. Specifically, due to niacinamide's amphiphilic nature, the molecule modulates the physical properties of the bacterial membrane and increases LL-37 bioavailability [77,79].…”
Section: Antimicrobial Activity Of Niacinamidementioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrated that keratinocytes treated with a niacinamide solution were successfully stimulated to synthesize AMPs in vitro, providing protection against skin infection [68]. Furthermore, there is evidence that niacinamide can potentiate the activity of cathelidicin LL-37 [77,79]. Specifically, due to niacinamide's amphiphilic nature, the molecule modulates the physical properties of the bacterial membrane and increases LL-37 bioavailability [77,79].…”
Section: Antimicrobial Activity Of Niacinamidementioning
confidence: 99%
“…Furthermore, there is evidence that niacinamide can potentiate the activity of cathelidicin LL-37 [77,79]. Specifically, due to niacinamide's amphiphilic nature, the molecule modulates the physical properties of the bacterial membrane and increases LL-37 bioavailability [77,79]. Of note, several studies correlated niacinamide's antimicrobial activity with increased neutrophil activity, demonstrating that niacinamide selectively enhanced the neutrophil killing of Staphylococcus aureus and Citrobacter rodentium [75,77,80].…”
Section: Antimicrobial Activity Of Niacinamidementioning
confidence: 99%
“…During viral infections, type-1 interferon (IFN), IFN-α, and IFN-β exert antiviral activity during viral infections, and CAMP/LL-37 exerts antiviral activity as well [43]. Vitamin D3 acts protectively during infections with several viral strains, including hepatitis viruses, the human immunodeficiency virus, and respiratory pathogenic viruses.…”
Section: Vitamin D3 and Natural Immunitymentioning
confidence: 99%